Injectable postoperative enzyme-responsive hydrogels for reversing temozolomide resistance and reducing local recurrence after glioma operation. (23rd June 2020) - Zhao, Zongren; Shen, Jiawei; Zhang, Long; Wang, Lansheng; Xu, Haoyue; Han, Yuhan; Jia, Jun; Lu, Yang; Yu, Rutong; Liu, Hongmei
Abstract : Glioma is the most aggressive primary malignant brain tumor. Abstract : Glioma is the most aggressive primary malignant brain tumor. The eradication of the gliomas by performing neurosurgery has not been successful due to the diffuse nature of malignant gliomas. Temozolomide (TMZ) is the first-line agent in treating gliomas after surgery, and its therapeutic efficacy is limited mainly due to the high activity levels of the DNA repair protein O 6 -methylguanine-DNA methyltransferase (MGMT) in glioma cells. Herein, we used an injectable matrix metalloproteinase (MMP) enzyme responsive hydrogel that loaded TMZ and O 6 -benzylamine (BG) (MGMT inhibitor) for eradicating residual TMZ-resistant gliomas after surgery. The hydrogels exhibited three features: (1) TMZ and BG could be encapsulated within the hydrophobic lamellae of the hydrogel to form Tm (TMZ + BG) hydrogels; (2) The hydrogels could release TMZ and BG in response to the high concentration of MMP enzymes after glioma surgery; (3) The hydrogels could increase local TMZ concentration and reduce side effects of BG. In vivo, the Tm (TMZ + BG) hydrogels inhibited the MGMT expression and sensitized TMZ-resistant glioma cells to TMZ. Moreover, the Tm (TMZ + BG) hydrogels effectively reduced the recurrence of TMZ-resistant glioma after surgery and significantly enhanced the efficiency of TMZ to inhibit glioma growth. Together, these data suggest that an MMP-responsive hydrogel is a promising localized drug delivery method to inhibit TMZ-resistant glioma recurrence after surgery.